ARTIFICIAL INTELLIGENCE DEVELOPMENT IN UZBEKISTAN: STRATEGIC VISION, ECOSYSTEM GROWTH, AND EMERGING APPLICATIONS - Nurbek Khatamov (Modern American Journals, 2025)
This article explores the rapid development of artificial intelligence (AI) in Uzbekistan, driven by national strategies, institutional reforms, and growing international cooperation. Following the approval of the “AI Development Strategy – 2030,” Uzbekistan has committed to building a robust digital ecosystem with a focus on AI research, education, infrastructure, and public-private sector applications. Key initiatives include the establishment of AI labs, training of over a million AI specialists, creation of high-performance computing infrastructure, and integration of AI technologies in governance, finance, transportation, and agriculture. Despite facing challenges in regulation and workforce development, Uzbekistan demonstrates strong political will and cross-sector collaboration to position itself as a regional AI innovation hub. The article provides a comprehensive analysis of policy goals, current implementations, and future outlook for AI in the country.
Keywords: Uzbekistan, Artificial Intelligence, AI Strategy, Digital Economy, Innovation, AI Ecosystem, Public Sector AI, ICT Development, AI Education, Central Asia, Smart Governance, Emerging Technologies.